An Introduction to Underwater Acoustics : Principles and Applications - Lurton, Xavier (Springer-Praxis books in geophysical sciences, 2010)
Sound waves are the only practical means of remote investigation of the sea and its bottom and transmission in seawater. Underwater acoustics has become one of the major technologies used in the exploration and exploitation of the oceans for scientific, industrial, or military/naval purposes. It is widely employed in the fields of ocean engineering, seafloor mapping, defence, oceanography, navigation, and fisheries. Dr Xavier Lurton is a renowned specialist in underwater acoustics. He has worked in this field as a scientist, engineer, project manager and teacher since 1981 and has participated in many scientific projects, systems developments and at-sea cruises. In the second edition of his book, Dr Lurton provides an updated and extended introduction to underwater acoustics, including coverage of the physical processes and their basic modeling, different underwater acoustic systems and their practical applications and a description and assessment of the various technologies. Dr Lurton has extensive experience as a lecturer in undergraduate and postgraduate schools, including naval academies. This book is based on his direct, first-hand experience of the many aspects of underwater acoustics in seas around the world, at the forefront of current research and development efforts